Isolation of Leptospira kirschneri serovar Grippotyphosa from a red panda (Ailurus fulgens) after antimicrobial therapy: Case report - LeCount, Karen; Fox, Kami; Anderson, Tammy; Bayles, Darrell O.; Stuber, Tod; Hicks, Jessica; Schlater, Linda K.; Nally, Jarlath E. (Frontiers in Veterinary Science, 2023)
A one-year-old female red panda started showing symptoms of illness, including lethargy, anorexia, abdominal discomfort, and vomiting, shortly after transfer to a new zoo. Serum was tested for leptospirosis using the microscopic agglutination test (MAT), and a titer of 1:25,600 to serogroup Grippotyphosa was detected. Antimicrobial treatment with doxycycline was initiated; after completion of treatment and resolution of clinical symptoms, a urine sample was collected to ensure clearance of leptospires and cessation of urinary shedding prior to co-housing with other red pandas. A repeat serum sample taken 13 days later had a lower titer of 1:6,400 to serogroup Grippotyphosa. A sample of the animal’s urine was cultured in HAN media and was culture positive for Leptospira. The recovered isolate was completely characterized by whole genome sequencing and serotyping with reference antisera, and the isolate was classified as Leptospira kirschneri serogroup Grippotyphosa serovar Grippotyphosa strain RedPanda1.